Big Nate : hug it out! - Peirce, Lincoln (Andrews McMeel Publishing, 2019)
In this full-color collection of comic strips, Nate Wright experiences a visit to the emergency room, a trip to the beach with his pals, and a new ride at the fair where he meets the girl of his dreams.